2016
DOI: 10.3892/mco.2016.1051
|View full text |Cite
|
Sign up to set email alerts
|

Conversion therapy for pancreatic cancer with peritoneal metastases using intravenous and intraperitoneal paclitaxel with S-1

Abstract: Abstract. Combination chemotherapy consisting of systemic and intraperitoneal agents against peritoneal metastases from several types of cancer has shown promising results. We herein report a case in which combination therapy with intravenous and intraperitoneal paclitaxel with S-1 converted an unresectable pancreatic cancer with peritoneal metastases into a resectable one. The patient was a 65-year old woman with recurrent pancreatitis for 5 months. Endoscopic ultrasonography-guided fine-needle aspiration rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Some reports have documented unresectable pancreatic cancer being converted into resectable disease with chemotherapy and prolonged overall survival after surgery [6][7][8][9][10][11][12][13]. We found 12 patients who underwent conversion surgery after neoadjuvant chemotherapy for pancreatic cancer initially diagnosed as unresectable ( Table 1).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some reports have documented unresectable pancreatic cancer being converted into resectable disease with chemotherapy and prolonged overall survival after surgery [6][7][8][9][10][11][12][13]. We found 12 patients who underwent conversion surgery after neoadjuvant chemotherapy for pancreatic cancer initially diagnosed as unresectable ( Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…Since 1997, gemcitabine has been the standard first-line treatment for patients with unresectable locally advanced or metastatic pancreatic cancer [4], but the rate of complete or partial response with gemcitabine ranges from 7 to 9.4% [3,5]. Few patients have undergone conversion surgery after chemotherapy for unresectable pancreatic cancer [6][7][8][9][10][11][12][13]. However, 2 recent trials of systemic chemotherapy in metastatic pancreatic cancer have shown promise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Currently, almost no effective therapy has been found to control or overcome this pathogenesis, 3,4 although intraperitoneal direct administration of anticancer drugs, such as paclitaxel, has been considered. 5 The postoperative occurrence of PM also has been associated with the therapeutic issue of surgery-induced shedding of cancer cells. 6 In some cases, presurgical endoscopic ultrasoundguided fine-needle biopsy can cause PM due to needle tract seeding.…”
Section: Introductionmentioning
confidence: 99%